2000
DOI: 10.1046/j.1440-1630.2000.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the outcome of occupational therapy: Tools and resources

Abstract: Current pressures to document outcomes and demonstrate the efficacy of occupational therapy intervention arise from fiscal restraints as much as from the humanitarian desire to provide the best quality health care to consumers. However, measuring outcomes is important in facilitating mutual goal setting, increasing the focus of therapy on the client, monitoring client progress, as well as demonstrating that therapy is valuable. The aims of this article are to provide the reader with an overview of what outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 41 publications
1
52
0
1
Order By: Relevance
“…A major challenge facing occupational therapy is identifying which process variables need to be measured, the best ways to do this and how processes and outcomes linked in a treatment session can be effectively measured. In answer to such a challenge, Unsworth (2000) provides an overview of outcomes research and a review of outcome assessments pertinent to occupational therapy in an attempt to inform therapists wishing to undertake outcomes research. The findings of the current study suggest that clinicians require specific continuing professional education programmes that provide opportunities for skill acquisition and practical application of the clinical outcomes research process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge facing occupational therapy is identifying which process variables need to be measured, the best ways to do this and how processes and outcomes linked in a treatment session can be effectively measured. In answer to such a challenge, Unsworth (2000) provides an overview of outcomes research and a review of outcome assessments pertinent to occupational therapy in an attempt to inform therapists wishing to undertake outcomes research. The findings of the current study suggest that clinicians require specific continuing professional education programmes that provide opportunities for skill acquisition and practical application of the clinical outcomes research process.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing demand worldwide that occupational therapy practice become evidence based (Bennett and Bennett, 2000;Cusick and McCluskey, 2000;Taylor, 2000). As a result, treatment effectiveness and outcome studies have been identified as key issues for the profession (Llorens and Gillette, 1985;Llorens and Snyder, 1987;Law, 1989a;Taylor and Mitchell, 1990;Timmerman et al, 1994;Unsworth, 2000). Active involvement of clinicians in clinical research has been advocated to facilitate professional practice that is grounded in theory and research, and provides quality care to our clients (Baum et al, 1984;Llorens and Gillette, 1985;Mitcham, 1986;Llorens and Snyder, 1987;Cusick, 1987Cusick, , 1994Cusick, , 2000Law, 1989a;Taylor and Mitchell, 1990;Rogers and Holm, 1994;Timmerman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Using outcome measures is a necessity for the occupational therapy profession, as it enables therapists to facilitate goal setting, monitor client's progress and decide on the most effective intervention (Unsworth, 2000). The use of outcome measures is also essential for evidence-based practice, which aims to the provision of the best quality health care to consumers (Unsworth, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The use of outcome measures is also essential for evidence-based practice, which aims to the provision of the best quality health care to consumers (Unsworth, 2000). Evidence-based practice is crucial for the purpose of demonstrating the value of occupational therapy and helping the profession to gain its unique and well-deserved place among the multi-disciplinary team (Powell, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Outcome measures should capture information about the sequelae of dysphagia such as client restrictions in social participation and/or feelings of distress; measuring only the impairment and activity limitation of the client may be limiting and fail to address the real concerns of the patient. It has been shown that an increase in societal participation may be more meaningful to a client than are changes at the impairment level [6][7][8][9][10][11][12]. Second, they must capture the areas in which speech pathologists focus therapy.…”
mentioning
confidence: 99%